536 Puzzles and Curious Problems - Dudeney, Henry E. (New York Charles Scribners sons, 1967)
Henry Ernest Dudeney was Englands greatest maker of puzzles. With respect to mathematical puzzles, especially problems of more than trivial mathematical interest, the quantity and quality of his output surpassed that of any other puzzlist before or since, in or out of England. This book contains almost the entire contents of two of Dudeneys best books, Modern Puzzles and Puzzles and Curious Problems, which have long been out of print and are extremely hard to obtain. The puzzles are presented in such a manner to attract readers who have only an elementary acquaintance with mathematics, as well as those who possess a more advanced knowledge of the science; and they are classified in such a way that the reader can easily satisfy his preference for any particular type: "Arithmetical and Algebraical Problems", "Geometircal Problems", "Combinatorial and Topological Problems", "Game Puzzles", Domino Puzzles", "Match Puzzles" and Unclassified Puzzles". Solutions are presented for each of the 536 problems in this huge collection.
Keywords: Science